2009
DOI: 10.1590/s0066-782x2009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Fatores genéticos na agregação familiar da pressão arterial de famílias nucleares portuguesas

Abstract: SummaryBackground: Despite of the increase in the prevalence of hypertension in Portugal, the importance of genetic factors in blood pressure (BP) has not been studied extensively in our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Moreover in selected populations the role of genetic factors appears to be likely predominant with respect to the environment 23, 24 . However the specific weight of familiarity is still underestimated for confounding factors in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in selected populations the role of genetic factors appears to be likely predominant with respect to the environment 23, 24 . However the specific weight of familiarity is still underestimated for confounding factors in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the greatest absolute BMI increase was within the already heaviest population [33], and only a moderate amount of SBP and DBP is accounted for by genetic factors [34], indicating the unignorable large impact of shared environment. Recently, Brown et al further added that, based on a US sibling cohort, sharing the same household could facilitate the social network influence on correlations in BMI [35].…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo observou-se que 18,6% dos escolares apresentavam elevações da pressão arterial, o que está em conformidade com alguns estudos nacionais recentes, os quais mostraram que a incidência dessa enfermidade pode variar bastante conforme a região estudada (12% a 44,7%), devido a diferenças metodológicas referentes aos métodos de amostragem, ao tamanho e características da amostra, à qualidade dos instrumentos de medida e à técnica empregada, e ainda ao número de aferições e pontos de corte para classificação da pressão arterial. Além disso, vale ressaltar que a incidência de HAS também sofre influência de variáveis intervenientes, dado o seu caráter multifatorial, que envolve tanto aspectos genéticos como ambientais (MAGALHÃES et al, 2002;FERMINO et al, 2009).…”
Section: Discussionunclassified